Preparation of Antimicrobial Hyaluronic Acid/Quaternized Chitosan Hydrogels for the Promotion of Seawater-Immersion Wound Healing - Wang, Xinlu; Xu, Pengcheng; Yao, Zexin; Fang, Qi; Feng, Longbao; Guo, Rui; Cheng, Biao (Frontiers in Bioengineering and Biotechnology, 2019)
Wound immersed in seawater with high-salt, high sodium, and high pathogenic bacteria, especially gram-negative bacteria, can cause serious infections and difficulties in wound repair. The present study aimed to prepare a composite hydrogel composed of hyaluronic acid (HA) and quaternized chitosan (QCS) which may promote wound healing of seawater-immersed wounds and prevent from bacterial infection. Based on the dynamic Schiff base linkage, hydrogel was prepared by mixing and oxidized hyaluronic acid (OHA) and hyaluronic acid-hydrazide (HA-ADH) under physiological conditions. With the addition of quaternized chitosan, oxidized hyaluronic acid/hyaluronic acid-hydrazide/quaternized chitosan (OHA/HA-ADH/O-HACC and OHA/HA-ADH/N-HACC) composite hydrogels with good swelling properties and mechanical properties, appropriate water vapor transmission rate (WVTR) and excellent stability were prepared. The biocompatibility of hydrogels was demonstrated by in vitro the fibroblast L929 cells culture study. The results of in vitro and in vivo studies revealed that the prepared antibacterial hydrogels could inhibit bacterial growth largely. The in vivo study further demonstrated that the antibacterial hydrogels exhibited high repairing efficiencies for the seawater immersed wound defect model. In addition, the antibacterial hydrogels decrease pro-inflammatory factors (TNF-α、IL-1β、IL-6) but enhance anti-inﬂammatory factors (TGF-β1) in wound. This work indicates that the prepared antibacterial composite hydrogels have great potential application in chronic wound healing, such as severe wound cure and open trauma infections.